A Comparison of Two Quail Abundance Indices and Their Relationship to Quail Harvest in Texas - Stephen J. Demaso; Markus J. Peterson; Jon R. Purvis; Nova J. Silvy; Jerry L. Cooke (National Quail Symposium Proceedings, 2017)
Surveys are used to monitor status and trends of animal populations. However, different surveys may give conflicting results for the same species and population being surveyed. Therefore, we compared results of the North American Breeding Bird Survey (BBS) and Texas Parks and Wildlife (TPW) roadside counts for scaled quail (Callipepla squamata) and northern bobwhite (Colinus virginianus) in Texas. Surveys were compared on both an ecoregion and statewide basis. The BBS and TPW surveys gave similar trends for bobwhites and scaled quail for 5 of 8, and 3 of 5 ecoregions, respectively. Survey trends differed at the statewide scale for both species. We compared estimated statewide harvest as an independent index of quail population status in Texas with results from both surveys. The TPW roadside survey was more closely related to estimated statewide harvest for northern bobwhites (R2 = 0.86, P <= 0.001) and scaled quail (R2 = 0.75, P = 0.0001) than the BBS survey (R2 = 0.60, P = 0.001; and R2 = 0.35, P = <0.0001, respectively). Survey methods, sampling frameworks, and issues of scale are important variables to consider when interpreting survey results. The BBS provides useful data on quail populations at a multi-state or national scale. However, most state wildlife agencies require surveys that provide information at finer spatial scales.
Keywords: Breeding Bird Survey; Callipepla squamata; Colinus virginianus; index; northern bobwhite; roadside survey; scaled quail; Texas